2022
DOI: 10.3892/etm.2022.11160
|View full text |Cite
|
Sign up to set email alerts
|

Docosahexaenoic acid improves altered mineralization proteins, the decreased quality of hydroxyapatite crystals and suppresses oxidative stress induced by high glucose

Abstract: Patients with type 2 diabetes mellitus (DM2) experience an increased risk of fractures and a variety of bone pathologies, such as osteoporosis. The suggested mechanisms of increased fracture risk in DM2 include chronic hyperglycaemia, which provokes oxidative stress, alters bone matrix, and decreases the quality of hydroxyapatite crystals. Docosahexaenoic acid (DHA), an omega-3 fatty acid, can increase bone formation, reduce bone loss, and it possesses antioxidant/anti-inflammatory properties. The present stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 47 publications
1
1
1
Order By: Relevance
“…In the absence of ECM and compared to normoglycemic condition, the mineralized matrix generated in the HG concentration displayed an increase in the mineral-to-matrix ratio and the type-B carbonate substitution level. The latter alteration (corresponding to a substitution of a phosphate by a carbonate group) is in agreement with the reduced calcium to phosphorus ratio already mentioned ( García-Hernández et al, 2012 ) and has also been recently reported using a human osteoblast cell line ( Cifuentes-Mendiola et al, 2022 ). Increased mineralization of the organic matrix is a feature of the cortical region of long bones in most rodent models of T2D ( Creecy et al, 2016 ; Hammond et al, 2014 ; Hunt et al, 2018 ).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In the absence of ECM and compared to normoglycemic condition, the mineralized matrix generated in the HG concentration displayed an increase in the mineral-to-matrix ratio and the type-B carbonate substitution level. The latter alteration (corresponding to a substitution of a phosphate by a carbonate group) is in agreement with the reduced calcium to phosphorus ratio already mentioned ( García-Hernández et al, 2012 ) and has also been recently reported using a human osteoblast cell line ( Cifuentes-Mendiola et al, 2022 ). Increased mineralization of the organic matrix is a feature of the cortical region of long bones in most rodent models of T2D ( Creecy et al, 2016 ; Hammond et al, 2014 ; Hunt et al, 2018 ).…”
Section: Discussionsupporting
confidence: 90%
“…In contrast, we ( Fig. 5 D) and others ( Cifuentes-Mendiola et al, 2022 ) show that HG exposure alone results in a higher carbonate substitution level; which indicates that other mechanisms are involved to modulate such change within the mineral. It should be noted that continuous insulin administration decreases the type B carbonate substitution in the bones of T2D rats independently of the restoration of glycemia, suggesting that lack of insulin effect may also be implicated in such defects ( Shi et al, 2021 ).…”
Section: Discussioncontrasting
confidence: 86%
“…There have been numerous similar studies conducted on this topic. [21] However, the topic of DHA's effects on bones is controversial despite research supporting its positive effects.…”
Section: Discussionmentioning
confidence: 99%